2000
DOI: 10.1038/sj.onc.1203469
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an interaction between the insulin receptor and Grb7. A role for two of its binding domains, PIR and SH2

Abstract: Grb7 is not a substrate of the insulin receptor tyrosine kinase activity. Grb7 binds the activated tyrosine kinase loop of the insulin receptors. Two domains of Grb7 are implicated in the insulin receptor binding: the SH2 domain and the PIR (phosphotyrosine interacting region). The role of these two domains in the interaction with the insulin receptor was already reported for Grb10 and Grb14, the other members of the Grb7 family of proteins. However, the relative importance of these domains varies, considering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 35 publications
4
45
0
1
Order By: Relevance
“…However, remarkably for all three Grbs the inhibitory effect on IR catalytic activity is mediated by the PIR, in agreement with a recent paper reporting an in vitro inhibitory effect of the BPS domain of Grb10 on the IR catalytic activity (45). It has been shown that the PIR and SH2 domains of the various Grb proteins are differentially implicated in the interaction with the IR (6). The SH2 domain is responsible for the binding of Grb7 to the IR, whereas both PIR and SH2 are equally important in the Grb10-IR interaction, and the PIR is the main binding domain in the IR-Grb14 interaction.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, remarkably for all three Grbs the inhibitory effect on IR catalytic activity is mediated by the PIR, in agreement with a recent paper reporting an in vitro inhibitory effect of the BPS domain of Grb10 on the IR catalytic activity (45). It has been shown that the PIR and SH2 domains of the various Grb proteins are differentially implicated in the interaction with the IR (6). The SH2 domain is responsible for the binding of Grb7 to the IR, whereas both PIR and SH2 are equally important in the Grb10-IR interaction, and the PIR is the main binding domain in the IR-Grb14 interaction.…”
Section: Discussionsupporting
confidence: 76%
“…Production of the GST Fusion Proteins-The GST-Grb14 (Grb14, PIR, SH2), GST-Grb7 (Grb7, PIR, SH2), and GST-Shc constructs were described previously (5,6). The mouse GST-Grb10␣ was a gift from J. Finidori.…”
Section: Methodsmentioning
confidence: 99%
“…Grb7 has both an SH2 and a PTB domain (58), each capable of binding to motifs containing a phosphorylated tyrosine (Fig. 8A).…”
Section: Coupling Of Caveolin-1 To the C-src Tyrosine Kinasementioning
confidence: 99%
“…In vitro tyrosine kinase assays have shown that the Grb7 family members inhibit the IR catalytic activity, and that Grb14 is the most potent inhibitor [10,11]. For all three Grbs, the inhibitory action on the IR kinase activity is mediated by a new interaction domain located between the SH2 and PH domains called either BPS (between PH and SH2) [12] or PIR (phosphorylated insulin receptor interacting region) [8,13]. PIR speci¢cally binds to the regulatory kinase loop of the IR.…”
Section: Introductionmentioning
confidence: 99%